2013
DOI: 10.1155/2013/583920
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Bispectral Index in Response to Experimental Noxious Stimuli in Adults under General Anesthesia

Abstract: Objective. Pain assessment is a major challenge in nonverbal patients in the intensive care unit (ICU). Recent studies suggest a relationship between the Bispectral Index (BIS) and nociceptive stimuli. This study was designed to examine changes in BIS in response to experimental noxious stimuli. Methods. Thirty participants under general anesthesia were in this quasiexperimental, within subject, pre- and poststudy. In the operating room (OR), BIS was monitored during moderate and severe noxious stimuli, induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Entropy processes raw cortical EEG and frontal EMG signals to produce two indices based on their frequency range, called ‘response entropy’ and ‘state entropy’. Although studies have shown that nociceptive stimulation increased BIS, response entropy and state entropy, this was heavily dependent on both the baseline BIS levels and the degree of concurrent hypnosis. It did not correlate with the quality or intensity of noxious stimuli , despite steady‐state, end‐tidal sevoflurane concentrations.…”
Section: Resultsmentioning
confidence: 95%
“…Entropy processes raw cortical EEG and frontal EMG signals to produce two indices based on their frequency range, called ‘response entropy’ and ‘state entropy’. Although studies have shown that nociceptive stimulation increased BIS, response entropy and state entropy, this was heavily dependent on both the baseline BIS levels and the degree of concurrent hypnosis. It did not correlate with the quality or intensity of noxious stimuli , despite steady‐state, end‐tidal sevoflurane concentrations.…”
Section: Resultsmentioning
confidence: 95%
“…[ 1 2 3 ] But it was still controversial whether BIS could be used in the assessment of the level of pain and adequacy of analgesia. [ 4 5 6 7 8 9 ] Some researchers think that BIS primarily measures the degree of sedation and sleep and does not reliably reflect the autonomic response to pain. In addition, BIS changes during nociceptive stimulation can be affected by many other variables such as sedatives, anesthetics, opioids (which decrease BIS by reducing cortical activity),[ 10 ] and neuromuscular blocking agents (which decrease BIS by reducing electromyogram [EMG] activity).…”
Section: Introductionmentioning
confidence: 99%
“…These indices are used to guide intraoperative anesthetic titration – from patient full wakefulness to light anesthesia but to a large extent do not convey enough information on the noxious stimulations during surgical procedures. For example, when noxious stimuli are applied, the BIS index can increase in some patients, decrease in some other patients, or stay unchanged 56 . Instead of relying on post-processed indices, several studies have recommended looking at raw electroencephalograms to identify changes in EEG band powers following noxious stimulations 57 .…”
Section: Current Methods For Evaluating Pain Under Anesthesia In the ...mentioning
confidence: 99%
“…For example, when noxious stimuli are applied, the BIS index can increase in some patients, decrease in some other patients, or stay unchanged. 56 Instead of relying on post-processed indices, several studies have recommended looking at raw electroencephalograms to identify changes in EEG band powers following noxious stimulations. 57 Patterns that are more frequently seen include an increase in EEG beta power (“beta arousal”), an increase in EEG delta power (“delta arousal”), and a reduction in EEG alpha power (“alpha dropout”).…”
Section: Current Methods For Evaluating Pain Under Anesthesia In the ...mentioning
confidence: 99%